PERSEPSI DAN PREFERENSI IKLAN MEMPENGARUHI NIAT BELI ANAK PADA PRODUK MAKANAN RINGAN - Sumarwan, Ujang; Simanjuntak, Megawati; Yurita, Yurita (Jurnal Ilmu Keluarga dan Konsumen, 2012)
This research was to analyze the differences between perception, preference, and purchase intentions based on treatment and gender;  influence of perception, preference, and consumption experience toward purchase intentions of children; influence of gender and treatment toward perception, preference, and purchasing intentions of children at snack products. This study use a factorial experiment design with two variables that is treatment (treatment 1 (T1): advertising exposure followed by consumer test, treatment 2 (T2): consumer test followed by advertising exposure) and gender (male and female). This research involved 60 school-aged children that was choosed by random sampling. The Independent sample t-test showed that child’s perception had significant difference significant between gender in treatment 1 and between treatment. Multiple linear regression analysis showed that perception, preference, and consumption experience influence significantly on purchasing intention of children. Two-Way ANOVA analysis also showed that perception was influenced by gender and interaction between gender and treatment.